Design, implementation and evaluation of RWTP-Gateway for FTP based data transfer - Tariq, Wajahat (My University, 2010)
The trend of video processing is increasing towards a digital arena and making use of distributions over the internet. Hence, movies in the near future will be more digitial and highly detailed. The new technology that is being used today is called as the 4K technology, where 4K refers to the high resolution of the movie which is 4096x2160 pixels. This resolution gives a more detailed image than what can be seen on commonly available HD-TVs, plasmas, computer screens or digital projection systems. This high resolution implies that a huge amount of data would be processed when transferred over the Internet, which in turn requires considerably large data rate, around 2.5 Gbps, in the presence of delay and packet loss. The Internet reliable transport protocol TCP cannot handle such data rate due to its limitations when considering its congestion control mechanism. This is where a Reliable WAN (Wide Area Network) Transport Protocol (RWTP), developed by the company \Deutsche THOMSON OHG", plays its role. RWTP has been shown to have the capability to transfer data at a rate of 5 Gbps over WAN even in the presence of delay and packet loss. Though, it lacks the ability to perform collaborative tasks with most commonly available applications like File Transfer Protocol (FTP). In this thesis work a proxy mechanism is implemented to make RWTP perform these collaborative tasks with one of the most commonly used applications; i.e. FTP in this case. An implementation scenario is completed in C++ and tested on 1 Gbps Ethernet network with 1 Gbps switches, 10 Gbps network routers and 10 Gbps network emulator to emulate delay and packet losses. Using 4K digital technology with 5000 frames where each frame is 50 MBytes gives a total of 250 GBytes data. The result of thesis work show that this amount of data can be transferred from Hannover, Germany to Los Angeles, United States in 42 minutes using RWTP-Gateway with FTP. On the other hand, with a direct FTP connection using TCP it takes 37 hours, but only 28 hours with a proxy-based FTP connection using TCP. Hence, RWTP-Gateway with FTP gives a significant reduction in transmission time by providing high speed data transfer with a factor of 50 in comparison with a direct FTP connection and with a factor of 40 in comparison with proxy-based FTP connection using TCP.
Keywords: Datorteknik; Computer Engineering